Asia-Australia distribution patterns among species of Mystrothrips (Thysanoptera, Phlaeothripinae), with two new species - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2018)
The genus Mystrothrips now comprises 10 species, of which one is from Brazil but the others from Asia and Australia, including M. brachystylis sp.n. and M. nomadus sp.n. from eastern Australia. Variation among specimens of M. dammermanni from sites in Southeast Asia and Queensland is discussed. Mystrothrips reteanum described from Korea and known from southern China, is here recorded from Fiji and eastern Australia, and moreover is newly recognized as a senior synonym of M. flavidus from Japan.